2021
DOI: 10.1002/cjce.24131
|View full text |Cite
|
Sign up to set email alerts
|

Dilute gas‐particle suspension in a diffuser: A two‐fluid modelling approach

Abstract: The present study evaluates the loss coefficient of a diffuser carrying a gassolid mixture with the volume fraction of the solid in the medium to upper limits of the dilute phase flow (solid volume fraction in the range of 0.005-0.10). In light of the computational analysis, it is observed that an increase in the concentration of the solid phase always helps in overcoming the losses despite a significant dissipation of energy due to collisions. Moreover, the loss coefficient lessens as the solid-phase density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Lighter particle movement was found to result in higher pressure recovery. Additionally, it was discovered that pressure recovery increased with an increase in the inlet slip velocity ratio [36][37][38][39][40][41][42].Further research [43] examined different area ratios and identified two conflicting effects on pressure recovery. Up to a critical area ratio value (9.97), pressure recovery increased, but it decreased beyond that point.…”
Section: Introductionmentioning
confidence: 99%
“…Lighter particle movement was found to result in higher pressure recovery. Additionally, it was discovered that pressure recovery increased with an increase in the inlet slip velocity ratio [36][37][38][39][40][41][42].Further research [43] examined different area ratios and identified two conflicting effects on pressure recovery. Up to a critical area ratio value (9.97), pressure recovery increased, but it decreased beyond that point.…”
Section: Introductionmentioning
confidence: 99%